A simple 2/3 modulation code and bit-flipping technique in bit-patterned media recording systems - Busyatras, Wiparat; Poompuang, Pitaya; Myint, Lin M.M.; Warisam, Chanon (My University, 2018)
Two-dimensional (2-D) modulation code is considered as one of the key schemes to improve the areal density capability for next generation magnetic recording e.g., bit-patterned media recording (BPMR) technology, due to its advantages such as severe inter-track interference (ITI) suppression and user densities escalation. In this work, a rate-2/3 2-D modulation with a three-reader three-track (3R3T) system is studied where the positions of reader are accordingly optimized with the encoded criteria to obtain the highest bit-error rate (BER) performance. Moreover, we also propose a bit-flipping technique which is one way to extremely improve the overall system performance. Here, the soft-information that are obtained from soft-output Viterbit algorithm (SOVA) detectors will be improved according with the encoded criteria before sending to the proposed decoder. Simulation results demonstrate that significant performance gain can be achieved using these two proposed approaches.
Keywords: 2-DModulation code; Bit-flipping technique; Bit-patterned media recording; Inter-track interference